2023
DOI: 10.2147/dddt.s389977
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol: A Potential Natural Lead Molecule for New Drug Design, Development and Therapy for Memory Impairment

Abstract: Celastrol is a naturally occurring chemical isolated from Tripterygium wilfordii Hook. f., root extracts widely known for their neuroprotective properties. In this review, we focus on the efficacy of celastrol in mitigating memory impairment (MI) in both in vivo and in vitro models. Scopus, PubMed and Web of Science databases were utilised to locate pertinent literatures that explore the effects of celastrol in the brain, including its pharmacokinetics, bioavailability, behavioral effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For instance, mangiferin, a natural glucoxilxanthone, has been found to show protective effects against memory impairment in animals and humans, without any side effects at the selected doses (Lum et al, 2021). Also, previous studies have suggested that the naturally occurring compounds genistein and celastrol are promising molecules for the development of neuroprotective drugs (Fuloria et al, 2022;Amir Yusri et al, 2023).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…For instance, mangiferin, a natural glucoxilxanthone, has been found to show protective effects against memory impairment in animals and humans, without any side effects at the selected doses (Lum et al, 2021). Also, previous studies have suggested that the naturally occurring compounds genistein and celastrol are promising molecules for the development of neuroprotective drugs (Fuloria et al, 2022;Amir Yusri et al, 2023).…”
Section: Open Access Edited Bymentioning
confidence: 99%